Ultrastructural organization of replicating chromatin in prematurely condensed chromosomes - Arifulin, E.A. (Вiopolymers and Cell, 2015)
Aim. The ultrastructural aspect of replicating chromatin organization is a matter of dispute. Here, we have analyzed the ultrastructural organization of replication foci using prematurely condensed chromosomes (PCC). Methods. To investigate the ultrastructure of replicating chromatin, we have used correlative light and electron microscopy as well as immunogold staining. Results. Replication in PCC occurs in the gaps between condensed chromatin domains. Using correlative light and electron microscopy, we observed that the replication foci contain decondensed chromatin as well as 80 and 130 nm globules, those were also found in condensed non-replicating chromatin domains. Using immunogolding, we demonstrated that DNA replication in S-phase PCC occurs in loose chromatin on the periphery of dense chromatin domains. Conclusion. Replication in PCC occurred in the decondensed chromatin neighboring the condensed chromatin without formation of special structures. Мета. До цих пір немає єдиної думки про ультраструктурі реплицирующихся хроматину. Ми проаналізували ультраструктурну організацію Реплікаційний фокуса в клітках з передчасно конденсованими хромосомами (ПКХ). Методи. Для вивчення хроматину на ультраструктурному рівні використовували методи кореляційної електронної та світлової мікроскопії, а також іммуноголдінг. Результати. Було показано, що реплікація в ПКХ відбувається в проміжках між доменами конденсованого хроматину. C допомогою кореляційної мікроскопії було встановлено, що в Реплікаційний фокусах присутній деконденсірованний хроматин і глобули діаметром 80 і 130 нм, так само присутні в конденсованих нерепліцірующіхся хроматінових доменах. Більш того, за допомогою іммуноголдінга було показано, що реплікація ДНК в S-фазних ПКХ відбувається в пухкому хроматині на периферії щільних хроматінових доменів. Висновки. Реплікація в ПКХ відбувається в деконденсірованном хроматині сусідить з конденсованим хроматином без утворення спеціальних структур. Цель. До сих пор нет единого мнения об ультраструктуре реплицирующегося хроматина. Мы проанализировали ультраструктурную организацию репликационного фокуса в клетках с преждевременно конденсированными хромосомами (ПКХ). Методы. Для изучения хроматина на ультраструктурном уровне использовали методы корреляционной электронной и световой микроскопии, а также иммуноголдинг. Результаты. Было показано, что репликация в ПКХ происходит в промежутках между доменами конденсированного хроматина. C помощью корреляционной микроскопии было установлено, что в репликационных фокусах присутствует деконденсированный хроматин и глобулы диаметром 80 и 130 нм, так же присутствующие в конденсированных нереплицирующихся хроматиновых доменах. Более того, с помощью иммуноголдинга было показано, что репликация ДНК в S-фазных ПКХ происходит в рыхлом хроматине на периферии плотных хроматиновых доменов. Выводы. Репликация в ПКХ происходит в деконденсированном хроматине соседствующем с конденсированным хроматином без образования специальных структур.